Vitamin D and autoimmunity - Amital, Howard (Henry Stewart Talks, 2010)
Effect of vitamin D on bone metabolism, Vitamin D affects many other systems including the immune system, Evolutionary significance of vitamin D, Effects on promoting proper immune homeostasis
Archived at 2020/12/10